Changes in HIV incidence among people who inject drugs in Taiwan following introduction of a harm reduction program: a study of two cohorts. - Yen-Fang Huang; Jyh-Yuan Yang; Kenrad E Nelson; Hsu-Sung Kuo; Chin-Yin Lew-Ting; Chin-Hui Yang; Chang-Hsun Chen; Feng-Yee Chang; Hui-Rong Liu (PLoS Medicine)
Background Harm reduction strategies for combating HIV epidemics among people who inject drugs (PWID) have been implemented in several countries. However, large-scale studies using sensitive measurements of HIV incidence and intervention exposures in defined cohorts are rare. The aim of this study was to determine the association between harm reduction programs and HIV incidence among PWID. Methods and findings The study included two populations. For 3,851 PWID who entered prison between 2004 and 2010 and tested HIV positive upon incarceration, we tested their sera using a BED HIV-1 capture enzyme immunoassay to estimate HIV incidence. Also, we enrolled in a prospective study a cohort of 4,357 individuals who were released from prison via an amnesty on July 16, 2007. We followed them with interviews at intervals of 6-12 mo and by linking several databases. A total of 2,473 participants who were HIV negative in January 2006 had interviews between then and 2010 to evaluate the association between use of harm reduction programs and HIV incidence. We used survival methods with attendance at methadone clinics as a time-varying covariate to measure the association with HIV incidence. We used a Poisson regression model and calculated the HIV incidence rate to evaluate the association between needle/syringe program use and HIV incidence. Among the population of PWID who were imprisoned, the implementation of comprehensive harm reduction programs and a lower mean community HIV viral load were associated with a reduced HIV incidence among PWID. The HIV incidence in this population of PWID decreased from 18.2% in 2005 to 0.3% in 2010. In an individual-level analysis of the amnesty cohort, attendance at methadone clinics was associated with a significantly lower HIV incidence (adjusted hazard ratio: 0.20, 95% CI: 0.06-0.67), and frequent users of needle/syringe program services had lower HIV incidence (0% in high NSP users, 0.5% in non NSP users). In addition, no HIV seroconversions were detected among prison inmates. Conclusions Although our data are affected by participation bias, they strongly suggest that comprehensive harm- reduction services and free treatment were associated with reversal of a rapidly emerging epidemic of HIV among PWID. Please see later in the article for the Editors' Summary.